Zwitterionic Metal Enolates or Equivalents: Generation and Capture - Zuo, Linhong; Guo, Wusheng (Synlett, 2022)
Functionalized ketones and their derivatives are important building blocks in organic synthesis and materials chemistry. The development of novel methods for the chemo-, regio-, diastereo-, stereo-, and enantioselective synthesis of functionalized ketones and their derivatives is a continuing endeavor of organic chemists. Here, we highlight a new approach recently initiated and developed by our group for the synthesis of (enantioenriched) ketones and related derivatives that is based on zwitterionic metal enolate chemistry.1 Introduction2 Annulations through Zwitterionic Palladium Enolate Chemistry for the Synthesis of Functionalized Cyclic Ketones3 Nucleophilic Capture of Zwitterionic Metal (Palladium or Copper) Enolates or Their Equivalents4 Conclusion
Keywords: ketones; zwitterionic metal enolates; cyclic carbonates; decarboxylation; cycloaddition